Some New Organotellurium(II) Molecular Adducts with Bidentate Ligands - Srivastava, Sekhar; Singh, Deepa (Asian Journal of Chemistry, 2010)
Thirty-six molecular adducts of the type RR´Te·L (where R = R´ = C6H5; R = R´ = (p-MeOC6H4); R=(p-MeOC6H4), R´ = (Me2NC6H4); R = (p-EtOC6H4), R´ = Me2NC6H4; R = R´ = C6H5CH2; RR´ = (C6H9)2 and L = bidentate Lewis base, i.e., 1,10, phenanthroline; 2,2&acute-bipyridine; bis(2-acetylpyrrole) phenylenediamine; bis(2-pyrrolecarboxylaldehyde) phenylenediamine; bis(2-pyridylcarboxylaldehyde) phenylenediamine and bis(2- naphthylaldehyde) phenylenediamine have been prepared and their structures have been established by elemental analysis, molar conductivity, IR and X-ray photoelectron spectroscopy.